The Pursuit of Success: Can Status Aspirations Negatively Affect Body Satisfaction? - SMITH, April R. (Institutional Knowledge at Singapore Management University, 2011)
The aim of the current study was to investigate whether weight and success interact to produce body dissatisfaction and disordered eating behaviors. To accomplish this aim, participants viewed pictures and read descriptions of women who varied in weight and career success. Participants who were high on status aspiration reported greater body dissatisfaction and ineffectiveness after being exposed to thin, successful women than did the participants who were low on status aspiration. Status aspiring participants, however, did not report greater drive for thinness, maturity fears, or bulimic symptoms. It is hoped that these findings will shed light on ways career women can pursue success without jeopardizing their health.